Managing multiple sclerosis in individuals aged 55 and above: a comprehensive review - Fernández, Óscar; Sörensen, Per Soelberg; Comi, Giancarlo; Vermersch, Patrick; Hartung, Hans-Peter; Leocani, Letizia; Berger, Thomas; Van Wijmeersch, Bart; Oreja-Guevara, Celia (Frontiers in Immunology, 2024)
Multiple Sclerosis (MS) management in individuals aged 55 and above presents unique challenges due to the complex interaction between aging, comorbidities, immunosenescence, and MS pathophysiology. This comprehensive review explores the evolving landscape of MS in older adults, including the increased incidence and prevalence of MS in this age group, the shift in disease phenotypes from relapsing-remitting to progressive forms, and the presence of multimorbidity and polypharmacy. We aim to provide an updated review of the available evidence of disease-modifying treatments (DMTs) in older patients, including the efficacy and safety of existing therapies, emerging treatments such as Bruton tyrosine kinase (BTKs) inhibitors and those targeting remyelination and neuroprotection, and the critical decisions surrounding the initiation, de-escalation, and discontinuation of DMTs. Non-pharmacologic approaches, including physical therapy, neuromodulation therapies, cognitive rehabilitation, and psychotherapy, are also examined for their role in holistic care. The importance of MS Care Units and advance care planning are explored as a cornerstone in providing patient-centric care, ensuring alignment with patient preferences in the disease trajectory. Finally, the review emphasizes the need for personalized management and continuous monitoring of MS patients, alongside advocating for inclusive study designs in clinical research to improve the management of this growing patient demographic.